PENGARUH PEMBERIAN PROMOSI KESEHATAN TERHADAP PENGETAHUAN IBU HAMIL TENTANG BAHAYA HIPERTENSI DI WILAYAH KERJA PUSKESMAS TANJUNG BATU KECAMATAN KUNDUR TAHUN 2018 - Yusdiana, Yusdiana; Mona, Silvia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Hypertension happens to be a high blood pressure measurement which is identified by systolic pressure of >140 mmHg and diastolic pressure of > 90 mmHg. The high blood pressure or also known as hypertension during pregnancy is tremendously risky for both mother and baby. This hypertension potentially causessome abnormalities such as inclined fetal growth, declining of consciousness, high-risk birth and thedecreasingof mother body defense.In fact, the incidence of hypertension in pregnant women specifically at the working area of Puskesmas Tanjungbatu is quite high which reached the number of 20 cases in 2017 and 22 cases in 2018. This research utilized Pre-test and Post-test design of Experiment group. The data were collected using a20-questions form of questionnaire to 62 respondents. The result shows the knowledge of pregnant women before health promotion on hypertension hazards is 1.1613, meanwhile after health promotion was given is 1.9677. From this finding, it is noted that there has been an escalation of 0.8064. And from the data test, p-value of 0.000 (p-value <0.05) is obtained, which means that there is a significant difference between average knowledge before and after the health promotion of the hypertension hazards to pregnant women in the Puskeskas Tanjungbatu in 2018.